Minority politics by other means: Assyrian militias in Iraq 2014–2017 - Drott, C (2021)
When the Islamic State in Iraq and Syria displaced Christian Assyrians from the Nineveh Plain in 2014, several militias were founded in response. These small groups aimed from the beginning to establish a presence on the ground after the defeat of their enemy, with the long-term goal to remain as security providers in their historical heartland. Lacking material resources or political power of their own, most militias tied themselves to a single ally affiliated with the Government of Iraq or the Kurdistan Regional Government — but others obtained support from several actors, or none. Considering the marginality of the political parties and political entrepreneurs behind the militias, those displaying loyalty to a single powerful ally could be expected to prevail against rival groups. Instead, a militia with weak ties to several actors established the strongest presence on the ground, and became the main security provider in the largest Assyrian town. To explain this puzzling outcome, the study provides a detailed account of how the militias formed, built their capacity, and deployed to the Nineveh Plain. The empirical data originates mainly from observations and interviews conducted in Iraq, as well as news and social media. With an inductive and iterative approach, the external relations of the militias emerged as the central explanation to address the research puzzle, but other factors are discussed as well. The study concludes that the most successful militia prevailed over its rivals by engaging multiple external actors with pragmatism and diplomatic skill, while tenaciously building a capable organisation. The findings demonstrate the potential of very small militias to exercise agency and assert themselves in an ongoing civil war.